Research on the Force Characteristics and Structural Optimization of Mine Antioutburst Door under the Influence of Coal and Gas Outburst Impact Airflow - Linchao Dai; Haitao Sun; Xusheng Zhao; Bo Wang; Jie Cao (Geofluids)
In order to deeply explore the destructive effect of the impulsive airflow on the mine antioutburst door when coal and gas outbursts occur in underground coal mines, a large-scale coal and gas outburst dynamic effect simulation experiment device is used to carry out the coal and gas outburst disaster simulation experiment. The impact load and deformation characteristics of the antioutburst door under the impact airflow during coal and gas outburst are analyzed, and the experimental results are discussed in depth through numerical simulation analysis and field example analysis. Based on this, the internal and external causes of the damage of the antioutburst door on the coal mine site are analyzed, the key technologies that need to be solved in the design of the antioutburst door’s disaster resistance are studied, and the overall design of the structure optimization design of the antioutburst door is proposed. The research results show that after coal and gas outburst, the pressure on the antioutburst door will rise and fall, and the fluctuation will be greater. Under the same installation position, the farther the antioutburst door is from the protruding point, the less pressure it bears. In the middle and late stages of the outburst, intermittent negative pressure of the gas at the antioutburst door appeared. The key technologies for the design of the antioutburst door and its disaster resistance mainly include that strengthen theoretical and experimental research on the formation mechanism of outburst shock waves in mines, the interaction mechanism between disaster shock loads and dampers, and the magnitude of disaster expected shock loads; optimize the structure of the antioutburst door size, the width of the contact surface between the air door and the door wall, the stress distribution of the air door under impact load, the design of the safety hole, and the locking device; and improve the disaster monitoring and alarm capabilities of the antioutburst door and collect changes in antioutburst door pressure in real time. The research results provide a theoretical basis and technical support for the optimization of the antishock performance of underground antioutburst doors in coal mines and have important practical significance for improving the disaster resistance of the ventilation system.